Pengaruh Pendekatan Kontekstual Berstrategi REACT terhadap Kemampuan Pemahaman Matematis dan Motivasi Belajar Siswa Sekolah Dasar - Halimatusadiah, Ai Meli Amelia (Mimbar Sekolah Dasar, 2017)
The low comprehension of elementary school students in integer material and the low motivation of students to learn mathematics is the background of this research. One alternative solution to the problem is to apply contextual approach with REACT strategy on learning mathematics. The purpose of this research is to determine the difference between the effect of contextual approach with REACT strategy compared with conventional learning on mathematical understanding ability and learning motivation of elementary school students on the matter of addition and reduction of integers. This research is a quasi-experiment with nonequivalent control group design. The results showed that both of it were able to improve the mathematical understanding ability and learning motivation of elementary school students, but contextual approach with REACT strategy was better and there is a positive correlation between learning motivation and mathematical understanding ability of students in the experimental class. Thus, it can be concluded that the contextual approach-player Chinese REACT effectively in improving the students’ mathematical understanding ability and learning motivation.